Influence of Ethylenediaminetetraacetic Acid (EDTA) on the Ability of Fatty Acids to Inhibit the Growth of Bacteria Associated with Poultry Processing - Hinton, A.; Ingram, K.D. (International Journal of Poultry Science, 2011)
The effect of Ethylenediaminetetraacetic Acid (EDTA) on the bactericidal activity of Fatty Acids (FA) was examined. A 0.5 M concentration of caproic, caprylic, capric, or lauric acid in 1.0 M Potassium Hydroxide (KOH) was supplemented with 0, 5, or 10 mM of EDTA and adjusted to pH 11.0 with citric acid. FA-KOH-EDTA was added to wells in agar seeded with 106 cfu/ml of Acinetobacter calcoaceticus, Aeromonas hydrophila, Campylobacter jejuni, Enterococcus faecalis, Escherichia coli, Listeria monocytogenes, Pseudomonas fluorescens, Salmonella typhimurium, or Staphylococcus simulans. Agar plates were incubated aerobically at 35°C for 24 h, except for C. jejuni plates which were incubated microaerophilically at 42°C for 48 h and zones of inhibition around the wells were measured. Results indicated that although caproic acid-KOH inhibited growth of C. jejuni only, caproic acid-KOH supplemented with EDTA produced significantly (p